1991
DOI: 10.5771/0023-4834-1991-3-302
|View full text |Cite
|
Sign up to set email alerts
|

Geschlechterpolitik im Wohlfahrtstaat: Aspekte im internationalen Vergleich

Abstract: In alkn westlichen Ländern sind Sozialstaat und Sozialpolitik angetreten, um die Folgen ungleicher VerhandJungspositionen, wie SIe' fur individualistische Erwerbsgesellschaften typisch sind, aufzufangen. Sie reagieren -sehr vereinfach! gesagtdarauf, daß niclH alle Menschen zu jeder Zelt, gleichermaßen und ohne Hilfe von anderen ihre ExiSlenz sichern können'. Indem bestimmte Personengruppen bzw. Bedarfslagen fruher oder später, mehr oder weniger vom Markt genommen, »dekommodifiziert« ) werden, hilft SOZialpolit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
5

Year Published

1992
1992
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 0 publications
0
18
0
5
Order By: Relevance
“…If we classify welfare states focusing on family policies and the way in which they structure gender and economic relationships through support of mother's employment, organization of care, the equal support of all forms of parenthood and partnership, and the promotion of "agency equality", i.e., the equal access of all persons to societal institutions that grant welfare (education, market, social security, care, etc. ), we arrive at a different classification of welfare-state regimes: The Nordic countries still largely constitute a welfare-state regime of their own, but the pattern of the conservative welfare states becomes more diverse, with France, Belgium, and partly the Netherlands being clearly set off against the German-speaking and the Mediterranean countries (Gornick, Meyers, and Ross 1997;Meyers, Gornick, and Ross 1999;Anttonen and Sipilä 1996;Lewis 1992;Langan and Ostner 1991;Neyer 2003aNeyer , 2005Korpi 2000). This implies that if we want to investigate the effect of family policies on fertility we cannot simply resort to pre-determined classifications of welfare states.…”
Section: Configurations Of Family Policies and Their Consequences Formentioning
confidence: 97%
See 1 more Smart Citation
“…If we classify welfare states focusing on family policies and the way in which they structure gender and economic relationships through support of mother's employment, organization of care, the equal support of all forms of parenthood and partnership, and the promotion of "agency equality", i.e., the equal access of all persons to societal institutions that grant welfare (education, market, social security, care, etc. ), we arrive at a different classification of welfare-state regimes: The Nordic countries still largely constitute a welfare-state regime of their own, but the pattern of the conservative welfare states becomes more diverse, with France, Belgium, and partly the Netherlands being clearly set off against the German-speaking and the Mediterranean countries (Gornick, Meyers, and Ross 1997;Meyers, Gornick, and Ross 1999;Anttonen and Sipilä 1996;Lewis 1992;Langan and Ostner 1991;Neyer 2003aNeyer , 2005Korpi 2000). This implies that if we want to investigate the effect of family policies on fertility we cannot simply resort to pre-determined classifications of welfare states.…”
Section: Configurations Of Family Policies and Their Consequences Formentioning
confidence: 97%
“…Following Esping-Andersen's (1990) approach to welfare-state analysis, feminist welfare-state researchers regard family policies as part of the state's policies to structure society (Orloff 1993;Lewis 1992;Langan and Ostner 1991 (Neyer 2003a). …”
Section: Configurations Of Family Policies and Their Consequences Formentioning
confidence: 99%
“…Welfare state theoreticians have explained the intra-country differences in fertility and employment behavior with the different attitudes of states towards working mothers (e.g., Langan and Ostner, 1991;Lessenich and Ostner, 1995;Anttonen and Sipilä, 1996;Ross, 1997, 1998;Esping-Andersen, 1999). By comparing institutional structures and public policies, they showed that state-aided measures help women to realize their potential income without foregoing their desire for children.…”
Section: Theoretical Considerations and Hypothesesmentioning
confidence: 99%
“…Since the 'conservatism' of these welfare regimes evolves not only from the central role of the family in care giving but also from the traditional gender division of labour within the family (cf. Langan and Ostner, 1991), we should expect a gendered variant of explicit or implicit familialism in conservative welfare regimes. But the historical case study of Belgium -as one of the conservative welfare regimes -will demonstrate that the character of familialism changes over time and for different fields of care.…”
Section: Varieties Of Familialismmentioning
confidence: 97%